Online Learning Analysis on the Application of Basketball Learning Process in High School - Rosanti Pradhita Ramadhani; Waluyo Waluyo (PHEDHERAL, 2021)
This research aims to find out and analyze the learning of the PJOK of basketball games. This study is a quantitative study using survey methods to find out the picture of PJOK online learning in basketball games. Data collection techniques use questionnaires and documents. The population in this study amounted to 169 learners, and samples were taken 20% of the population so that a sample of 35 learners was obtained. The data obtained is then analyzed and tested the validity of data using the SPSS 22 program. The results of the analysis from the study of online learning survey PJOK basketball game in students of class XII IPS Sma Negeri 5 Surakarta can be seen by many learners. This is aimed at the number of respondents who answered well as many as 13 respondents (37%), very good as 8 respondents (23%), less good as 10 respondents (29%), and who answered badly as many as 4 respondents (11%). Concluded from this study, Online Learning PJOK Basketball Games for the effectiveness of online learning PJOK basketball games are in a good category.